A Rehabilitation Framework for Children Living With HIV in South Africa: Reaching Consensus for a Resource-Poor Community. (March 2020) - Maddocks, Stacy; Hanass-Hancock, Jill; Cobbing, Saul; Chetty, Verusia
Abstract: Although rehabilitation frameworks for adults living with HIV are developing steadily, interventions to ensure the integration of rehabilitation into the routine care of children living with HIV-related disabilities lags. We sought to explore perceptions of, and gain expert consensus on, a rehabilitation framework for children living with HIV. Experts in HIV pediatric care in South Africa engaged in a Delphi survey, based on findings from a context-specific rehabilitation framework for adults. Consensus was determined by an a priori threshold of 80% agreement and an interquartile range of 1 or lower on criteria to be included as essential or useful in the framework. Experts agreed that enhancing access to patient-centered care through decentralization and training of health care and community care workers in the use of disability screening tools at each point of care needed to be included in the framework. Strengthening multiprofessional team collaboration was also seen as fundamental.